b - Richards, Graham (London : Routledge, 2009)
"Key Concepts in Psychology provides an accessible and comprehensive guide to the major terms and concepts encountered in psychology. Each entry is placed alphabetically for ease of use and gives a clear definition followed by relevant examples, links to further reading, and website references that point to additional resources for study."
Includes bibliographical references and index.
Keywords: Psychology -- Dictionary -- English